2008
DOI: 10.1093/carcin/bgn108
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4 promotes laryngeal and hypopharyngeal squamous cell carcinoma metastasis through MMP-13-dependent invasion via the ERK1/2/AP-1 pathway

Abstract: Laryngeal and hypopharyngeal squamous cell carcinomas (LHSCCs) are common head and neck cancers with a high propensity for lymph node (LN) and lung metastasis. Here, we report that LHSCCs express high levels of functional CXCR4 receptors, native for chemokine stromal cell-derived factor-1 (SDF-1/CXCL12). Primary tumor immunohistochemistry from LHSCC patients has revealed significant expression of CXCR4 and CXCL12. Greater expression of CXCR4 but not that of CXCL12 is correlated with LN and distant metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
78
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 45 publications
8
78
2
Order By: Relevance
“…While Luo et al found CXCR4 overexpression to be associated with metastatic LSCC [22], no differences in CXCR4 expression were observed between cancer tissue and counterpart normal tissue in the present study, and no relationship was found with cancer lymph node metastasis. The reason for this discrepancy may be that while both Tan et al [38] and Luo et al [22] found their group of laryngeal cancer samples to contain more lymph node positive samples, 63% of the samples in our group were lymph node negative. CXCR4 overexpression could potentially act as an indicator of lymph node metastasis, but additional studies are needed.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…While Luo et al found CXCR4 overexpression to be associated with metastatic LSCC [22], no differences in CXCR4 expression were observed between cancer tissue and counterpart normal tissue in the present study, and no relationship was found with cancer lymph node metastasis. The reason for this discrepancy may be that while both Tan et al [38] and Luo et al [22] found their group of laryngeal cancer samples to contain more lymph node positive samples, 63% of the samples in our group were lymph node negative. CXCR4 overexpression could potentially act as an indicator of lymph node metastasis, but additional studies are needed.…”
Section: Discussioncontrasting
confidence: 66%
“…Many studies have reported that various malignancies, including those of the lung and kidney, use chemokine pathways to disseminate cancer cells to target organs [41]. Sev-eral studies have indicated that the CXCR4/CXCL12 axis also plays a crucial role in promoting metastasis in laryngeal cancer [38]. CXCR4 encodes C-X-C chemokine receptor 4, a member of GPCR receptor family which is found to be overexpressed in many cancer types such as HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 phosphorylates caspase-9 at Thr125 then inhibits caspase-9 processing and caspase-3 activation [42]. Inhibition of ERK1/2 phosphorylation is proved to blockade CXCL12-induced FaDu migration and chemoinvasion, suggesting that activation of ERK1/2 is an important step in the signal that leads to increased migration and chemoinvasion of HNSCC [43]. A very recent research showed that ERK1/2 MAPK mediated FaDu cell death via a caspase-independent mechanism [44].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies of HNSCC cell lines have demonstrated that CXCL12 can stimulate proliferation and invasion. 45 Further analysis of the mechanism of induction of proliferation indicates that CXCL12 induces ERK activation through transactivation of the EGFR and can occur through release of EGFR ligands. 41,46,47 ADAM17/TACE has been associated with tumor progression in oral squamous cell carcinoma 48 and other cancers, 49,50 and can cleave multiple EGFR ligands, including TGF-␣, HB-EGF, and AREG.…”
Section: In Vivo Invasion Of Hnscc 2863mentioning
confidence: 99%